2010
DOI: 10.4067/s0718-27912010000200001
|View full text |Cite
|
Sign up to set email alerts
|

Soil Glycosidase Activities and Water Soluble Organic Carbon Under Different Land Use Types

Abstract: The purpose of this study was to measure the effects of different land uses on soil glycosidase activities (α-and β-glucosidase, α-and β-galactosidase), water soluble organic carbon (WSOC) and their relationships. Glycosidase activities showed significant differences under different land use types, the highest one was woodland. β-glucosidase had the highest activity among the four glycosidases. The activities of these glycosidases decreased with increasing soil depth, being all significantly affected by change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…Moreover, nutrient deficiency is a common constraint for microorganisms living in tailings. An initial comparison (climatic factors were not considered) showed that the average SOC of the tailings samples was far less than the values reported for natural and arable soils 18 19 20 and close to those of highly contaminated soils 21 .…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, nutrient deficiency is a common constraint for microorganisms living in tailings. An initial comparison (climatic factors were not considered) showed that the average SOC of the tailings samples was far less than the values reported for natural and arable soils 18 19 20 and close to those of highly contaminated soils 21 .…”
Section: Discussionmentioning
confidence: 82%
“…The correlations of enzyme activity with soil properties tended to change with incubation time, in most cases without statistical significance (p > 0.05, data not shown), with the exception of MUBglucosidase activity whose correlation with OM became significant after 8 h of extraction (r = 0.5660; p < 0.08) and the significant (p < 0.05) correlation of acetate-glucosidase activity with OM, that is, in general, kept with time. Some other researchers have found correlations between enzyme activity (MUB) and soil pH and/or clay content (Avellaneda-Torres et al, 2013;Ma et al, 2010). In spite of the significant correlation between MUB and maleate buffers, no significant relationship (p < 0.05) was obtained for the former and any soil property.…”
Section: Results and Discussion 31 Evaluation Of Different Buffers Amentioning
confidence: 84%
“…The decrease in SOC following a land use change is difficult to predict due to variations in the factors that drive SOC mineralization, among them, forest type, climate, soil properties, biochemical environment, and soil management practices (Hombegowda, van Straaten, Köhler, & Hölscher, ; Wei et al, ). SOC content was similar in S forest , O +manure , and O ‐manure , probably because perennial vegetation contributes to continuous and higher C input in soil through root exudation compared to annual crops, such as maize (Ma et al, ). The addition of organic inputs may also have contributed to maintaining similar levels of SOC in cactus soils, although this should not be the main reason, because maize soils also received organic inputs.…”
Section: Discussionmentioning
confidence: 97%